The Idea of Minimum Protection of Socioeconomic Rights under the ECHR - Milašiūtė, Vygantė (Teisė, 2020)
The article examines to what extent and how the protection of socioeconomic rights can be and is actually effected under the ECHR. This is done taking into account the fact that only minimum protection of some socioeconomic rights is necessary for the realization of the ECHR rights.
Keywords: socio-economic rights; ECHR; indivisibility of rights; effectiveness of rights; minimum protection